FEATURES OF THE REFRACTIVE INDEX OF POROUS SILICON WITH GRADIENT POROSITY - A. P. Hakoyan; S. V. Melkonyan
The refractive index of inhomogeneous porous silicon layers has been calculated, taking into account the dispersion law and configurations of pores and using the approximation of effective medium.
Keywords: Physics; Optics